Bogumił Hoff (1829-1894) - "odkrywca" Wisły. Red. Renata Czyż. - Wisła 2014 [recenzja] - Ogłoza, Ewa (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2015)
Bogumił Hoff (1829-1894) - "odkrywca" Wisły. Red. Renata Czyż. - Wisła 2014 [recenzja]